1988
DOI: 10.1177/074823378800400205
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetics and Bioavailability of Paraquat in Rats following Different Routes of Administration

Abstract: The toxicokinetics and bioavailability of[14C]paraquat were examined in rats which had received a single dose (11.6 μg/kg) of the herbicide by the iv, intragastric, dermal or pulmonary route. In the pulmonary route studies, rats were exposed to an aqueous solution or liquid aerosols of[14C]paraquat through a tracheal cannula or [14C]paraquat aerosols in a nose-only inhalation chamber. After intratracheal, intragastric, and dermal administration of[14C]paraquat to the rat, the average bioavailabilities were 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The paraquat plasma concentrations we observed following an oral dose in FVB mice were approximately a magnitude less than what has been observed following an intraperitoneal dose to C57BlJ/6 mice; correspondingly, the paraquat brain concentrations we observed were also lower (Prasad et al, 2007(Prasad et al, , 2009Breckenridge et al, 2013). Paraquat has highly variable bioavailability depending upon the route of administration, with the majority of an oral dose found in the feces, which may explain some of the differences in observed plasma concentrations in the different mouse strains (Daniel and Gage, 1966;Chui et al, 1988). …”
Section: Discussionmentioning
confidence: 38%
“…The paraquat plasma concentrations we observed following an oral dose in FVB mice were approximately a magnitude less than what has been observed following an intraperitoneal dose to C57BlJ/6 mice; correspondingly, the paraquat brain concentrations we observed were also lower (Prasad et al, 2007(Prasad et al, , 2009Breckenridge et al, 2013). Paraquat has highly variable bioavailability depending upon the route of administration, with the majority of an oral dose found in the feces, which may explain some of the differences in observed plasma concentrations in the different mouse strains (Daniel and Gage, 1966;Chui et al, 1988). …”
Section: Discussionmentioning
confidence: 38%
“…Other studies using radiolabeled PQ found that it was absorbed by all exposure routes tested, including intravenous, intragastric, dermal, and pulmonary (Chui et al 1988; Dey et al 1990). PQ in brain after oral dosing was previously demonstrated in rat and the concentration was higher after 10 doses compared with 1, supporting its accumulation (Widdowson et al 1996).…”
Section: Discussionmentioning
confidence: 93%
“…Wearing PQ‐soaked underwear would cause prolonged exposure to PQ, which might partly explain the high concentration of PQ in cardiac blood. PQ distribution in the postmortem tissues could be related to many factors, such as the time between exposure and death , the route of exposure , and the medical treatment . To better understand the distribution characteristics of PQ in humans, more human data are needed.…”
Section: Resultsmentioning
confidence: 99%